The - Duanmu, San (Oxford University Press, 2000)
This is the first comprehensive study of Chinese phonology. Duanmu has brought us an accessibly written text that introduces relevant theories in a non-technical way. He covers several areas that were previously thought to be absent in Chinese, or were not considered phonological issues. It also offers new analyses of several traditional topics, such as the phonemic inventory, allophonic variation, syllable structure, the [r] suffix, tone, and Tone 3 Sandhi